PENGARUH MOTIVASI, DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA APARATUR SIPIL NEGARA DI KANTOR KEMENTERIAN AGAMA KABUPATEN SITUBONDO - Hardjono Hardjono; Sakinatul Fitriya (Growth, 2020)
This study aims (1) to determine the effect of motivation, work discipline and competence partially influence the performance of ASN (2) to determine the effect of motivation, work discipline and competence simultaneously affect the performance of ASN (3) to find out among the variables of motivation, work discipline and competencies that have the most dominant influence on ASN performance. The method used in this research is quantitative method. The results of the research from multiple linier regression equation Y = 1,083E-16 + 0,182X1 + 0,568X2 + 0,226X3 + e. Partially motivation variable is 2,102, work discipline value is 2,321. These three variables have a significant positive effect on ASN performance. Simultaneously the motivation, work discipline and competence variables have a positive effect on the ASN performance variable. It can beseen from 31,577 > 2,77. The most dominant influential variable is the work discipline variable with a value of 5,542.